Enabling the use of alternative materials in road construction - Nunes, Manuel Clemente Mendonça (1997)
Alternative materials represent an important potential source of aggregates for road construction. At present, their use remains limited owing to the abundance and low cost of high quality natural aggregates, low costs of landfill disposal and generally restrictive specifications for pavement materials. Nevertheless, their influence in relation to the primary aggregates is likely to increase in the future with the enforcement of more strict environmental regulations at national and European levels. The objective of this research project was to investigate a wide range of alternative materials and provide a practical framework for their assessment enabling pavement engineers to deal with most applications in road construction.